2013
DOI: 10.1590/s0036-46652013000500012
|View full text |Cite
|
Sign up to set email alerts
|

PROTECTIVE EFFECT OF THE PROBIOTIC Saccharomyces boulardii IN Toxocara canis INFECTION IS NOT DUE TO DIRECT ACTION ON THE LARVAE

Abstract: SUMMARYIn a previous study our group found that the probiotic Saccharomyces boulardii was capable of reducing the intensity of infection in mice with toxocariasis. In order to assess whether the mechanism involved would be a direct action of the probiotic on Toxocara canis larvae, this study was designed. Both probiotics were singly cultivated in plates containing RPMI 1640 medium and T. canis larvae. S. boulardii and B. cereus var. toyoi cultures presented 97.6% and 95.7% of larvae with positive motility, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Changes in microbial diversity in the environment might potentially be of importance for response to helminths, as it has been demonstrated that gut microbiota can alter the response to Toxocara in mice. 40 The age effect in our study, with Toxocara seroprevalence increasing with age in the offspring generation, might reflect a time trend rather than a biological age patterns, and decreasing seroprevalence of Toxocara in more recent birth cohorts is presented in Figure 1. Similar trends were observed for Ascaris.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Changes in microbial diversity in the environment might potentially be of importance for response to helminths, as it has been demonstrated that gut microbiota can alter the response to Toxocara in mice. 40 The age effect in our study, with Toxocara seroprevalence increasing with age in the offspring generation, might reflect a time trend rather than a biological age patterns, and decreasing seroprevalence of Toxocara in more recent birth cohorts is presented in Figure 1. Similar trends were observed for Ascaris.…”
Section: Discussionmentioning
confidence: 64%
“…This may imply that early‐life exposure to Toxocara is a risk factor for development of allergic disease and that the risk resulting from this exposure may not be lifelong. Changes in microbial diversity in the environment might potentially be of importance for response to helminths, as it has been demonstrated that gut microbiota can alter the response to Toxocara in mice …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, E. faecalis CECT71219 at different doses of 7 × 10 4 (CFU/g), 1.46 × 10 4 CFU in culture and 1 × 10 8 CFU fed in mice showed both in vitro and in vivo larvicidal activity [ 44 ]. In contrast, Avila et al [ 45 ] reported that none of the Saccharomyces boulardii and Bacillus cereus var . toyoi showed in vitro effects against T. canis larvae.…”
Section: Trends Of Probiotics Against Helminth Zoonosismentioning
confidence: 97%
“…It is important to clarify that the time points of 24 and 48 h were selected based on prior study in which S. boulardii action in just 48 h of infection . In the same study, a group of animals was kept receiving probiotic up to 60 days after infection and was observed that the reduction rate was similar to the observed at 48 h. This result suggests that the probiotic action might occur in the first 48 h. The mechanism of action of this probiotic is unknown, what is known so far is that S. boulardii does not exert a direct effect on the parasite larvae . Considering that S. boulardii modulates the structure and the activity of adhesions of the intestinal mucosa and these effects could contribute to the enhancement of intestinal cell restitution , this study aimed to understand the possible immunomodulatory mechanism of S. boulardii in mice experimentally infected by T. canis .…”
Section: Introductionmentioning
confidence: 97%